Synthesis and Characterization of CDS/SIO2 Nanocomposites - Salem, Aeshah Nizar (2010)
Core-shell nanocomposites are gaining lots of interest due to their potential application in different field like catalysis, sensor, electronic, biomedical ect. In addition, they show better properties when two different element nanoparticles coating each other than a single nanoparticles is used. In this thesis, we studied the synthesis Rout and characterization of CdS/PVA nanoparticles by hydrothermal method with different concentration of cadmium acetate deposited in a PVA matrix. SiO2 nanoparticles by the sol-gel method with different concentrations of TEOS and CdS / SiO2core-shell nanocomposites by encapsulation Stober method. The result obtain by analysis of the product of CdS/PVA, SiO2 and CdS / SiO2core-shell nanocomposites have successful. The result of X-ray diffraction (XRD) analysis shows the cubic and hexagonal structure of the CdS nanoparticles, amorphous phase of SiO2 and CdS/SiO2 core-shell nanocomposites, The electrical properties including the d.c. conductivity of CdS/PVA were found to be 2 x 10-7 S/cm, and optical band gap energy 2.53 eV respectively. To improve conductivity of SiO2 nanoparticles when prepared CdS/SiO2 nanocomposites were found to be 6 x 10-10 S/cm . The FTIR measurement absorption centred at 690 cm-1 corresponding to the Cd–O. And at 1200 cm-1 is assigned to Si-O group. However, The peak of PVA/CdS/SiO2 particles was wider at about 3500 cm–1.The morphology of nanopatricles and nanocomposite study by (TEM) mentioned that the composites were estimated as being from 5-15 nm for CdS, 25- 140 nm for SiO2, and the CdS/SiO2 was estimated to be around 15 nm for the core and above 30 nm for the shell.